Food purchasing behavior in Surkhet, Nepal: Shopping practices, food perceptions, and aspirations - Gupta, Ishika; Avula, Rasmi; Kole, Subir; Boncyk, Morgan; Isanovic, Sejla; Vecci, Joseph; Khan, Asfand Yar (CGIAR, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a district-level multi year assessment. Using data collected in March- April 2023, this data note describes who is shopping for food in households, frequency, place of purchase, reasons for preferences for places of purchase, and perceptions about food. This is one of a set of data notes that together provide a holistic picture of the agrifood system on the themes of climate, gender, production, markets, and diets in the district.